Chemical synthetic biology. (1st March 2014) - Chiarabelli, Cristiano; Luisi, Pier Luigi
Although both the most popular form of synthetic biology (SB) and chemical synthetic biology (CSB) share the biotechnologically useful aim of making new forms of life, SB does so by using genetic manipulation of extant microorganism, while CSB utilises classic chemical procedures in order to obtain biological structures which are non-existent in nature. The main query concerning CSB is the philosophical question: why did nature do this, and not that? The idea then is to synthesise alternative structures in order to understand why nature operated in such a particular way. We briefly present here some various examples of CSB, including those cases of nucleic acids synthesised with pyranose instead of ribose, and proteins with a reduced alphabet of amino acids; also we report the developing research on the "never born proteins" (NBP) and "never born RNA" (NBRNA), up to the minimal cell project, where the issue is the preparation of semi-synthetic cells that can perform the basic functions of biological cells.